Implikasi Diplomasi Pertahanan terhadap Keamanan Siber dalam Konteks Politik Keamanan - Ar rahman, Lazuardi Luqman (Jurnal Diplomasi Pertahanan, 2020)
The development of global technology and information gave an impact on the increasement of Cyber media users which allow them to connect with each other without any obstacles by using the Internet, this of course presents a new threat to the security of a country. The openness and freedom offered by cyber media makes it difficult for the state to monitor and supervise cyber space which is considered too broad, making cybersecurity a complex topic where actors, motives and targets vary and always evolving every day. Security politics are an inseparable part of this discussion because the use of state security concept is a fundamental component in drafting regulations and policies. This research aims to explain the relation between the complexity of cybersecurity, the role of political security and defense diplomacy. Qualitative method and literature study technique is used in this research. This research uses the assistance of defense diplomacy theory and the concept of national security which serves as a tool to dissect existing problems. From this research, the researcher can conclude that the complexity of cybersecurity encourages political security actors to take responsibility in protecting citizens from various security threats including cyber threats, through defense diplomacy in the form of signing an MoU regarding a Transfer of Knowledge with other countries.